O domínio cultura amazônica à luz da organização e representação da informação - Rodrigues, Anderson Luiz Cardoso (2011)
Explores and analyses the Amazon culture domain in the organization and information representation context. It presents concepts of culture highlighting schools of thoughts aiming on basing reflections about the studied domain. The supportive theorical reference is focused in the Ranganathan s Faceted Classification Theory and in the Theory of Integrated Levels from the Classification Research Group, as the theorical-methodological basis as for outlining the classificatory structure aiming on building documentary language in the Amazon culture domain. The selection of concepts took place based on the terms resulted from an oral research in three geographical municipalities in Amazon, Bragança, Castanhal and Marajó archipelago. Etymological origins analysis of the words indicated the influence of foreign culture from the European, African, Asiatic and American continents in the Amazon language. The results of that analysis revealed the feasibility of developing a working methodology in order to outline a classification structure and a set of concepts to represent the Amazon culture domain in its fundamental roots as a basis for the building of a system for knowledge organization.